Comparison of serum biochemical parameters in children with febrile seizures - Gaurang Dilipkumar Pabani; Pragya Prakash Chandra Khanna (Indian Journal of Child Health, 2021)
Background: Febrile convulsions are the most common provoked seizures affecting children. Low magnesium level leads to cell and membrane excitability thereby causing seizures. Objective: The objective of the study was to determine the role of serum sodium, calcium, magnesium, and zinc in children with simple febrile seizures (SFSs). Materials and Methods: This was a case–control study done in children admitted in the pediatric ward. Children with SFSs were taken as cases while children with fever but without seizures served as controls. After obtaining informed consent, details of each child were recorded, which included age, sex, seizure details (duration, type), nature of the febrile illness, and history of febrile seizures (FSs). Estimation of serum sodium, zinc, magnesium, and calcium was done. Results: The present study included 120 subjects, out of which 60 were cases and 60 were controls. The male-to-female ratio was 2:1. In our study, there was no significant difference in the levels of calcium, magnesium, and zinc in cases with FSs and controls. Although the serum zinc levels were in the normal range, majority of the children with SFS had serum zinc levels toward the lower range of normal which was statistically highly significant. Conclusion: Our study found that SFSs occurred more frequently in boys. The levels of serum calcium and magnesium were normal and did not correlate with SFS. Low serum zinc level had a direct correlation with SFS, although this level was within the defined normal range.